Sueños de Tánger: Extraterritorial Basque Crime Fiction on Immigration to Spain - Shanna Lino (Studies in 20th & 21st Century Literature, 2019)
As the world increasingly turns its attention to the European refugee crisis and to the 1.8 million who have arrived on that continent since 2014 as a consequence of being forced to flee their native countries’ war-torn cities and villages, questions continue to arise regarding the ethical and political responsibilities of Western nations to facilitate this exodus and to provide refugee and immigration services en route and at destination. Spain remains the intended port of arrival for thousands of Malians, Mauritanians, Moroccans, and Western Saharans who sometimes manage to escape war and extreme poverty only to find themselves stalled on their voyage to the promised land, trapped in the no-man’s-lands of refugee camps or the port-city ghettos of neighboring developing nations. The misery, tensions, and violence that arise within these makeshift immigration centers is the subject of Basque writer Jon Arretxe’s third crime novel translated into Spanish: Sueños de Tánger (Tangerko ametsak, 2011), which focuses on the plight of the undocumented that precedes their arrival on Spanish soil. Given the tragic probability of so many of those who eventually manage to set foot in a patera, the Moroccan-set novela negra invites the opportunity to intersect that eventuality and suggests a Spanish ethical responsibility to do so. This paper analyzes the geographic, ethical, and diegetic borders that are negotiated, imagined, and transgressed in Arretxe’s novel within the context of Spanish genre fiction and demonstrates the manners in which Sueños de Tánger visually navigates the Moroccan city’s medina and the Malian capital Bamako’s communes in order to decenter the Spanish reading public to postcolonial territories that remain historically and ethically bound to Spain’s imperial legacy.
Keywords: transit city; migration; extraterritorial interdiction; handheld narration; crime fiction; Spain; Basque; Tangier; Bamako